Using the Medical Research Council framework to develop a complex intervention to improve delivery of care for young people with Type 1 diabetes. Issue 6 (12th April 2013) - Eiser, C.; Johnson, B.; Brierley, S.; Ayling, K.; Young, V.; Bottrell, K.; Whitehead, V.; Elliott, J.; Scott, A.; Heller, S.
Abstract Aims We describe how we have used the development phase of the Medical Research Council (MRC) Guidelines to construct a complex intervention to improve physical and psychological health among young people (16–21 years) with Type 1 diabetes. Methods We consulted previous reviews where available and conducted systematic searches of electronic databases to determine physical and mental health among the population, audited medical records, surveyed self‐reported psychological health among our clinic population; and interviewed staff (n = 13), young people (n = 27) and parents (n = 18) about their views of current care. Results Our audit (n = 96) confirmed a high HbA1c [86 mmol/mol (10.0%)] and one third (36.1%) reported significant eating problems. Young people did not attend 12% of their clinic appointments. Staff described difficulties communicating with young people who wanted staff to take account of their individual lifestyle when giving information. Conclusion Based on the findings of the systematic reviews and our audit, we concluded that there was sufficient evidence to justify development of a model of care specific to this age group. The components of the complex intervention include changes to standard care, an optional 5‐day self‐management course directed at young people and a separate family communication programme. The MRC Guidelines provided a valuable structure to guide development and evaluation of this intervention.